Научное обоснование путей модернизации электроприводов газоперекачивающих агрегатов - Крюков, Олег Викторович (НТУ "ХПИ", 2013)
The basic aspects of the system approach to designing and modernization of electric drives of main gas pipelines compressor stations are considered. Factors of power efficiency for successful realization of the new technical solutions providing complex automation, power savings and reliability of compressor stations gas compressor units operation are presented and scientifically proved.
Keywords: магистральные газопроводы; компрессорные станции; бесперебойный транспорт газа; пропускная способность газопровода; промышленные системы ЭГПА; факторы энергоэффективности